Exopolymers in bacterial adhesion: interpretation in terms of DLVO and XDLVO theories - Azeredo, Joana (1999)
Exopolymers have an important role in bacterial adhesion and are associated with irreversible adhesion. Moreover, they can coat surfaces enhancing or avoiding bacterial colonisation. To study the role of exopolymers in the adhesion of bacteria to glass, three mutants of Sphingomonas paucimobilis (which are high (TR), medium (CV) and low (F72) exopolymer producers), were used. The adhesion tests were performed in phosphate saline buffers and in solutions of the exopolymer produced by each mutant. The DLVO theory was able to explain the results in phosphate saline buffers, although this theory could not explain the results obtained in the presence of the exopolymer. The XDLVO theory enabled the interpretation of the results in the presence of the exopolymer, where hydrophobic interactions played an important role. However, polymeric interactions that are not taken into account in these two theories are also expected to be determinant in the adhesion process.